The Family Bereavement Program: Description of a theory-based prevention program for parentally-bereaved children and adolescents - Ayers, Tim S. (Omega (Westport), 2013)
This article describes a preventive intervention to promote resilience of parentally bereaved youth. This intervention includes separate but concurrent programs for youth and caregivers that were developed to change empirically-supported risk and protective factors. We first discuss the risk that parental death confers to youth mental health and social adaptation outcomes. Next, we discuss the theoretical framework underlying this program. After describing the content and structure of the program, we describe the results of an experimental field trial and discuss directions for future work.